Adaption of microbial life to environmental extremes : novel research results and application - Stan-Lotter, Helga; Fendrihan, Sergiu (Springer, 2017)
This entirely updated second edition provides an overview on the biology, ecology and biodiversity of extremophiles. Unusual and less explored ecosystems inhabited by extremophiles such as marine hypersaline deeps, extreme cold, desert sands, and man-made clean rooms for spacecraft assembly are presented. An additional focus is put on the role of these highly specialized microorganism in applied research fields, ranging from biotechnology and nanotechnology to astrobiology. Examples such as novel psychrophilic enzymes, compounds from halophiles, and detection strategies for potential extraterrestrial life forms are discussed in detail. The book addresses researchers and advanced students in the fields of microbiology, microbial ecology and biotechnology.
Keywords: Extreme environments -- Microbiology.; Adaptation (Biology); elektronické knihy; electronic books